2021
DOI: 10.1007/s12070-021-02616-7
|View full text |Cite
|
Sign up to set email alerts
|

Virucidal effect of povidone iodine on COVID-19 in the nasopharynx: an open-label randomized clinical trial

Abstract: Povidone-iodine (PVP-I) is a time-tested antiseptic agent with excellent virucidal (99.99%) properties. Repurposing it against coronavirus disease-19 (COVID-19) is a relatively newer concept and has been sparsely tested in vivo. The most common route of entry of severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) is the nasopharynx. Averting colonization of the virus could be one of the best options to reduce the incidence of infection. PVP-I gargle and mouthwash were found to be effective in vitro ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…Iodine compounds have been previously reported to bring about changes in the viral coat by modifying histidine and tyrosine amino acids leading to impairment of the attachment phase [ 31 ]. The present findings are consistent with the studies performed on MERS coronavirus and SARS-CoV-2 where researchers found iodine compounds to be clearing the viral load in cell-culture suspension assays, oral cavity, skin surface, and nasopharyngeal wash [ 23 , 24 , 32 , 33 , 34 ]. The present study’s findings may pave the way for the repurposing of Renessans, which is already approved for the treatment of ulcerative conditions (European Patent Specification 2011).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Iodine compounds have been previously reported to bring about changes in the viral coat by modifying histidine and tyrosine amino acids leading to impairment of the attachment phase [ 31 ]. The present findings are consistent with the studies performed on MERS coronavirus and SARS-CoV-2 where researchers found iodine compounds to be clearing the viral load in cell-culture suspension assays, oral cavity, skin surface, and nasopharyngeal wash [ 23 , 24 , 32 , 33 , 34 ]. The present study’s findings may pave the way for the repurposing of Renessans, which is already approved for the treatment of ulcerative conditions (European Patent Specification 2011).…”
Section: Discussionsupporting
confidence: 93%
“…A concentration containing 1% active ingredient showed complete virucidal effect on salivary secretions [ 24 ]. The results of virucidal activity remained promising when the formulation was tested via nasal irrigation for nasopharyngeal wash as well [ 33 ]. Apart from other formulations of iodine, Renessans composition has also been tested for antiviral potential for influenza virus and hepatitis C virus [ 21 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other than this preventive trial [ 13 ], most studies that examined the efficacy of povidone-iodine enrolled cohorts ranging from 4 to 189 participants [ 48 , 52 ]. Some of these studies measured virus load from nasopharyngeal samples [ 13 , 44 , 47 , 49 ], while others measured virus load in saliva [ 48 , 45 , 51 ]. As few studies correlated their cycle threshold (Ct) values with virus load, data from existing studies cannot be pooled to reliably compare the overall effects of povidone-iodine on virus load.…”
Section: Methodsmentioning
confidence: 99%
“…In a clinical trial involving 735 participants who received povidone-iodine (0.45% concentration), none reported local irritant effects of povidone-iodine despite applying povidone iodine throat spray 3 times daily to the throat for 42 d [ 13 ]. Although largely self-limited nasal tingling has been reported in some studies [ 44 , 47 , 68 ], data from one clinical trial did not observe alterations in nasal function or detectable damage to the ciliated epithelium [ 69 ].…”
Section: Methodsmentioning
confidence: 99%
“…Povidone iodine (PVP-I) can be safely used in the nose at concentrations up to 1.25% and in the mouth at concentrations up to 2.5% for a maximum of 5 months [24] . PVP-I is a proven antiseptic agent with excellent virucidal properties (99.99%) [25] , dilute solutions of PVP-I have historically been used in Asia to treat upper respiratory tract infections [26] . Antiseptic nasal and oral PVP-I solutions are effective in inactivating SARS-CoV-2 at a variety of concentrations after exposure times of 60 seconds [27,28] .…”
Section: Povidone Iodinementioning
confidence: 99%